Physicochemical, conformational properties and ACE-inhibitory activity of peanut protein marinated by aged vinegar. (March 2019) - Guo, Shanguang; Ai, Minmin; Liu, Jielang; Luo, Zifeng; Yu, Jiayi; Li, Ziqi; Jiang, Aimin
Abstract: The purpose of this paper was to study the effect of vinegar marinating, a Chinese traditional method, on the physicochemical, conformational properties, and angiotensin converting enzyme (ACE) inhibitory activities of peanut protein, so as to provide understandings to produce functional foods. Results of surface hydrophobicity and of fluorescence emission spectra demonstrated that the hydrophobicity of the soaked peanut protein was weakened or decreased. Fourier transformation infrared (FTIR) data indicated that marinating led to a more flexible structure of peanut protein droplet, because the secondary structure β-sheet was decreased and α-helix was increased in the marinated peanut. Compared to the native peanut, the marinated peanut had higher ACE-inhibitory activities and was more susceptible to enzyme during digestion process for the low content of β-sheet. Moreover, because more small peptides (∼5.5 kDa) were produced, ACE-inhibitory capacities of the marinated were enhanced more in vitro mimic gastrointestinal digestion than was done the native. This study shows that vinegar marinating enhances the ACE inhibition ability of peanut protein by altering its stereo structure, and this enhanced ability is stable after digestion and even increased, suggesting that vinegar marination is a valuable method of producing bioactive peptides. Highlights: Aged vinegar marinating decreased β-sheet and increased α-helix content of peanut protein. The modified protein was endowed with higher ACE-inhibitory activity (p < 0.05). The modified protein was susceptible to in vitro gastrointestinal digestion. The endowed higher ACE-inhibitory activity was substantial and strengthened after digestion.